APLIKASI PENCARIAN PROPERTI DI JAKARTA DENGAN METODE ANALYTIC NETWORK PROCESS DAN TOPSIS - Yagyu Munenori M.E.; Viny Christanti Mawardi; Novario Jaya Perdana (Fakultas Teknologi Informasi Universitas Tarumanagara, 2022)
There have been several buying and selling applications that are intended to help bring together buyers, sellers, or agents in finding the house criteria needed. But there are still conditions where buyers find it difficult to find the house or property of their dreams. At the same time sellers are also difficult to find the right buyer. For that we need an application that can realize a search application with property recommendation features that can be used to find the best unit that suits their wishes. The methods used are the Analytic Network Process and TOPSIS methods. The ANP method is used because of the consideration of the interrelationships between elements at different levels. TOPSIS method is also used to be able to display more accurate results in terms of ranking. From the recommendation test, 90% of the 10 tests were obtained and the percentage result was 94.1% from 17 respondent tests. Based on these tests, it is known that the error occurred because the data was not found. The absence of property data in accordance with the Criteria can be caused by filling out invalid criteria and can also be caused by a lack of variation in property data.